2019
DOI: 10.3390/rs11161873
|View full text |Cite
|
Sign up to set email alerts
|

Mapping the Spatial-Temporal Dynamics of Vegetation Response Lag to Drought in a Semi-Arid Region

Abstract: Drought, as an extreme climate event, affects the ecological environment for vegetation and agricultural production. Studies of the vegetative response to drought are paramount to providing scientific information for drought risk mitigation. In this paper, the spatial-temporal pattern of drought and the response lag of vegetation in Nebraska were analyzed from 2000 to 2015. Based on the long-term Daymet data set, the standard precipitation index (SPI) was computed to identify precipitation anomalies, and the G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(23 citation statements)
references
References 73 publications
1
21
0
1
Order By: Relevance
“…The analysis of the spatial distribution of time lag between the emergence of meteorological drought and response of vegetation covers to it shows that the late response times (i.e., time lags more than two months) are mostly associated with tree cover land use types (particularly forests consisting evergreen trees), while there is also a positive correlation between the response time of vegetated covers to the agricultural droughts and the density of their green leaves. The late response time of trees to drought events is mostly because of the root system of trees that allows them to have access to more stable water resources and meanwhile supports them by nutrient uptakes during drought events [65,66]. These findings are consistent with previous studies that showed similar results in different case studies that vegetation covers of forests may respond to meteorological droughts with a time lag and also remain for a longer period after their termination from a meteorological point of view [67,68].…”
Section: Discussionsupporting
confidence: 90%
“…The analysis of the spatial distribution of time lag between the emergence of meteorological drought and response of vegetation covers to it shows that the late response times (i.e., time lags more than two months) are mostly associated with tree cover land use types (particularly forests consisting evergreen trees), while there is also a positive correlation between the response time of vegetated covers to the agricultural droughts and the density of their green leaves. The late response time of trees to drought events is mostly because of the root system of trees that allows them to have access to more stable water resources and meanwhile supports them by nutrient uptakes during drought events [65,66]. These findings are consistent with previous studies that showed similar results in different case studies that vegetation covers of forests may respond to meteorological droughts with a time lag and also remain for a longer period after their termination from a meteorological point of view [67,68].…”
Section: Discussionsupporting
confidence: 90%
“…The behavior patterns of the VIs in the forests respond to summer rains, where the highest values were observed and that correspond to the growing season, NDVI, SAVI, MSAVI, and EVI increase appreciably during the beginning and the end of the season of growth [50]. Forests have a longer response of lag to other types of vegetation, when they face extreme weather; their own responses to stress and their adaptability make them less influenced by climatic anomalies and have a lag response to prolonged drought due to their deep root system [51]. In the case of grasslands, there is a tendency to decrease in the values of the VIs, for the dry seasons, seasonality of precipitation, and more specifically, the proportion of total precipitation in summer, is related to the productivity of grasses [52], the lack of water can cause the grass to appear dry and straw, which affects the sensitivity of the VIs to the color.…”
Section: Discussionmentioning
confidence: 99%
“…With the rapid advancement of remote sensing technology, global-scale land surface parameters, derived from long time series of remote sensing observations, have provided a good description of vegetation changes [11][12][13]. Leaf area index (LAI), defined as onehalf the total developed area of green leaves per unit horizontal surface area, can serve as a proxy for detecting vegetation greenness and serves as a measure of the amount of vegetation that is vertically distributed [14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%